ANALISIS PENGENDALIAN KUALITAS RUBBER PADA PROSES PRODUKSI WIPER PADA PT VALEO AC INDONESIA-BATAM: ANALISIS PENGENDALIAN KUALITAS RUBBER PADA PROSES PRODUKSI WIPER PADA PT VALEO AC INDONESIA-BATAM - Asmara, Doni; Fajrah, Nofriani (LPPM Universitas Putera Batam, 2019)
ABSTRAK Wiper is one component of the trunk used to clean the dirt in the mirror from rain or other dirt. Because technology development will emerge between companies. One of the wiper components produced by PT Valeo AC Indonesia-Batam is rubber with various types and sizes. The quality of rubber swept on the car glass affect the cleanliness of the car glass from dirt or rainwater. In the production process there is still a demaged product, it is necessary to analyze the demage product data and evaluate the data processing result using the Statistical Process Control (SPC) method. The purpose of this study is to analyze the defects occurring in rubber product. This study uses p-control chart to analize the number of defective product from the processing data indicating that there is data out of control limits. To analyze the cause of the defect, fishbone diagrams are applied to defects occuring in rubber product.On the control chart there is one defective data that is out control limit of 53 data with an avarage p value of 0.33361. Factors affecting defects in rubber based on analysis are human, machines, materials, environments and method, this study is expected to be useful for companies to improve the quality of rubber and customer satisfaction.